2012
DOI: 10.1073/pnas.1113931109
|View full text |Cite
|
Sign up to set email alerts
|

Climate change, adaptive cycles, and the persistence of foraging economies during the late Pleistocene/Holocene transition in the Levant

Abstract: Climatic forcing during the Younger Dryas (∼12.9-11.5 ky B.P.) event has become the theoretical basis to explain the origins of agricultural lifestyles in the Levant by suggesting a failure of foraging societies to adjust. This explanation however, does not fit the scarcity of data for predomestication cultivation in the Natufian Period. The resilience of Younger Dryas foragers is better illustrated by a concept of adaptive cycles within a theory of adaptive change (resilience theory). Such cycles consist of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(84 citation statements)
references
References 42 publications
1
83
0
Order By: Relevance
“…The Resilience Theory model is widely used in Ecology and to some extent in Archeology, and has proved to be a useful tool for analyzing the interlinked social-ecological systems that are adaptive and enduring in a deep-time perspective (Gunderson and Holling, 2001;Holling, 2001;Redman, 2005;Dearing, 2008;Rosen and Rivera-Collazo, 2012). At the core of Resilience Theory are the adaptive cycles, which move dynamically through four phases, described as α-, r-, K-, and Ω-phases.…”
Section: Climate Change and Social Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Resilience Theory model is widely used in Ecology and to some extent in Archeology, and has proved to be a useful tool for analyzing the interlinked social-ecological systems that are adaptive and enduring in a deep-time perspective (Gunderson and Holling, 2001;Holling, 2001;Redman, 2005;Dearing, 2008;Rosen and Rivera-Collazo, 2012). At the core of Resilience Theory are the adaptive cycles, which move dynamically through four phases, described as α-, r-, K-, and Ω-phases.…”
Section: Climate Change and Social Processesmentioning
confidence: 99%
“…Many studies based their environmental determinism on the major restructuring of vegetation resulting from climatic fluctuation, and proposed that the shift to wild-cereal cultivation was a response of hunter-gatherers to the Terminal Pleistocene Younger Dryas (YD) climatic deterioration (Wright, 1993;Bar-Yosef and Belfer-Cohen, 2002;Rosen and Rivera-Collazo, 2012). Some works even refer to this as a collapse of Natufian foraging systems (Weiss and Bradley, 2001;Burroughs, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the wider Levant region people's adaptation and mitigation strategies to a changing climate during the transition from the last glacial period into the Holocene interglacial have been widely discussed in relation to the beginnings of agriculture (e.g. Rosen, 2007;Blockley and Pinhasi, 2011;Maher et al, 2011a;Rosen and Rivera-Collazo, 2012). Yet our understanding of how the Levant experienced this global transition in climate is still somewhat unclear (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have suggested deteriorating climate conditions impacted cultures (Büntgen et al, 2011;Huntley et al, 2002;Magny, 2004;Rosen and Rivera-Collazo, 2012;Williams et al, 2015), the selection…”
Section: Introductionmentioning
confidence: 99%